ethics of the teacher in the environments learning virtuals (Revista Electrónica REDINE, 2018)
This essay focuses in a reflective perspective regarding the Teachers' Ethics in Virtual Learning Environments. It is emphasized that ethics characterize what is a moral act, as how it is rationally justified to be categorized as "good" or "bad" in a coordinated system of values. The teaching experience also involves axiological structures as it has real impact on the ethical foundations of students. A teacher in virtual learning environments must model and foster an ethical structure inspired by Responsibility, Honesty, Solidarity, Respect and Equity, so that on the basis of them and of Knowing, Doing and Being, an integral strengthening as a human being is promoted and achieved.
Keywords: ethics of teachers; coordinated system of values; virtual learning environments